PEMILIKAN TERNAK DI LINGKUNGAN PEKARANGAN TELUKNAGA, CITEUREUP DAN PACET - S. ADISOEMARTO; SRI PARYANTI WALUJO; WORO A. NOERDJITO (BERITA BIOLOGI, 1985)
S. ADISOEMARTO, SRI PARYANTI-WALUJO& WORO A.NOERDJITO. 1985. Domestic animal ownership within the kitchen gardens in Teluk naga, Citeureup and Pacet.Berita Biologi 3(2) : 70- 75. Surveys on domesticated animals in kitchen gardens were conducted in Teluknaga,Citeureup and Pacet in West Java in the middle of 1980.There were 13 kinds of animals listed. Each kind of these animals has been analysed on the bases of number of owners,rearing intensity and pattern of distribution in each locality. The most popular and widely distributed animals were chickens. This animal might be crowned as the "prima dona" of the kitchen garden environment.